Availability Optimization of CO-Shift Conversion System of a Fertilizer Plant using Genetic Algorithm Technique (Bangladesh Journal of Scientific and Industrial Research, 2010)
This paper discusses the availability optimization of CO shift conversion system of a fertilizer plant using Genetic Algorithm. The fertilizerplant comprises of various systems viz. shell gasification and carbon recovery, desulphurization, CO-shift conversion, decarbonation-CO2cooling, CO2 removal, nitrogen wash and ammonia synthesis etc. One of the most important functionaries of a fertilizer plant is CO shiftconversion system. The CO shift conversion system of a fertilizer plant has four main subsystems, arranged in series. Considering exponentialdistribution for the probable failures and repairs, the mathematical formulation of the problem is done using probabilistic approach anddifferential equations are developed on the basis of Markov birth-death process. These equations are then solved using normalizing conditionsso as to determine the steady state availability of the CO shift conversion system. The performance of each subsystem of CO shift conversionsystem of a fertilizer plant has also been optimized using Genetic Algorithm. So, the findings of the present paper will be highlyuseful to the plant management for the timely execution of proper maintenance decisions and hence to enhance the system performance.Key words: Performance optimization, CO shift conversion, Genetic algorithm.DOI: 10.3329/bjsir.v45i2.5711Bangladesh J. Sci. Ind. Res. 45(2), 133-140, 2010